Efektifitas Penerapan Perangkat Pembelajaran Fisika Dasar Berbasis Keterampilan Berpikir Kritis Menggunakan Aplikasi Edmodo Berplatform Android - Zainudin, Zainudin; Pambudi, Buyung (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2019)
The Effectiveness of the Application of Basic Physics Learning Devices Based on Critical Thinking Skills Using the Edmodo Platform on Android. The purpose of this study is to describe the effectiveness of the application of basic physics learning devices based on critical thinking skills using the Android platform Edmodo application. This research is a pre-experimental study with the research design used namely One Group Pretest Postest Design. The research subjects were 16 second semester students of the 2018 - 2019 academic year STKIP PGRI Mathematics Education Study Program Bangkalan subject matter of temperature and heat. The results of critical thinking skills at the pretest and posttest experienced a significant increase having N-Gain 0.6 in the moderate category. The results of the positive student responses to learning questionnaires were 86.4%. It can be concluded that the application of basic physics learning devices based on critical thinking skills using the android platform EDMODO application can improve students 'critical thinking skills and students' positive responses to learning so that they can be said to be effective.